2014
DOI: 10.1523/jneurosci.2567-14.2014
|View full text |Cite
|
Sign up to set email alerts
|

Inhibiting ACAT1/SOAT1 in Microglia Stimulates Autophagy-Mediated Lysosomal Proteolysis and Increases Aβ1–42 Clearance

Abstract: Acyl-CoA:cholesterol acyltransferase 1 (ACAT1) is a resident endoplasmic reticulum enzyme that prevents the buildup of cholesterol in membranes by converting it to cholesterol esters. Blocking ACAT1 pharmacologically or by Acat1 gene knock-out (KO) decreases amyloidopathy in mouse models for Alzheimer's disease. However, the beneficial actions of ACAT1 blockage to treat Alzheimer's disease remained not well understood. Microglia play essential roles in the proteolytic clearance of amyloid ␤ (A␤) peptides. Here… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
97
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 90 publications
(102 citation statements)
references
References 93 publications
(2 reference statements)
2
97
0
Order By: Relevance
“…We found that in cultured mouse microglia, Acat1 KO or an ACAT1 inhibitor K604 ( Figure 1A) [81] upregulated lysosome biogenesis and enhanced degradation of oligomeric Aβ1-42 [99]. We also showed that Acat1 KO in microglia stimulated oligomeric Aβ1-42 clearance in the mouse brain in vivo [99]. These results suggest that in addition to reducing Aβ production, blocking ACAT1 may benefit AD by stimulating Aβ clearance in microglia.…”
Section: Acat1 Blockage On Aβ1-42 Degradation In Microgliamentioning
confidence: 73%
See 4 more Smart Citations
“…We found that in cultured mouse microglia, Acat1 KO or an ACAT1 inhibitor K604 ( Figure 1A) [81] upregulated lysosome biogenesis and enhanced degradation of oligomeric Aβ1-42 [99]. We also showed that Acat1 KO in microglia stimulated oligomeric Aβ1-42 clearance in the mouse brain in vivo [99]. These results suggest that in addition to reducing Aβ production, blocking ACAT1 may benefit AD by stimulating Aβ clearance in microglia.…”
Section: Acat1 Blockage On Aβ1-42 Degradation In Microgliamentioning
confidence: 73%
“…Recently Shibuya et al in this laboratory investigated whether ACAT1 blockage enhanced oligomeric Aβ1-42 clearance in microglia. We found that in cultured mouse microglia, Acat1 KO or an ACAT1 inhibitor K604 ( Figure 1A) [81] upregulated lysosome biogenesis and enhanced degradation of oligomeric Aβ1-42 [99]. We also showed that Acat1 KO in microglia stimulated oligomeric Aβ1-42 clearance in the mouse brain in vivo [99].…”
Section: Acat1 Blockage On Aβ1-42 Degradation In Microgliamentioning
confidence: 75%
See 3 more Smart Citations